Social Cognition in focus: considerations on biological and cultural aspects (Research, Society and Development, 2020)
Investigations about gender/sex differences and their repercussions on social cognition are a relevant and current topic. This paper intends to present an initial approach to research in this area by analysing studies that focus on the relationship between sex differences and the neural bases of the theory of mind. To support the analysis, a literature review was conducted, resulting in 4 publications comprising the set of texts for analysis. The findings in the literature seem to point to differences in the recruitment of areas in the theory of mind neural bases due to sex differences. At the same time, however, some central issues still need to be enlightened by future investigations, such as, 1) the interpretation of the nature of the differences found, as well as the articulation between biological and cultural aspects in this process, and 2) the relationships between differences in the neural bases of the theory of mind, mindreading performance and social behaviour.